The Role Of BTS Endorsements In The Decision To Purchase Kenangan Coffee - Sriwanti Belanti; Nurhidayah Layoo (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
The purpose of this study is to investigate and evaluate the impact of brand image on consumer motivation for Kopi Kenangan X BTS purchases as well as the mediating role of celebrity endorsers. Explanatory research was used in the design of the study. The respondents in the study were Indonesian Twitter users who are fans of BTS. Purposive sampling was employed to select 103 respondents for the sample. The data analysis technique used in this study, which computes using SPSS 22 software, is path analysis. The findings of the study demonstrate that: Celebrity endorsers significantly and favorably impact brand image.